Nutritional and Sensory Profiling of Circular Food Product Innovation Through Lush Bites: Utilizing Marine-Agricultural Waste for Sustainable Consumption - Nafisah Zainuba Hasan; Adisa Naila Lubna (JFCN: Journal of Food, Culinary, and Nutrition, 2025)
The growing issue food waste that responsible for an estimated 7,29% of Indonesia’s greenhouse gas emissions in Indonesia over the past 20 years, demands urgent action.  This food waste can be repurposed into a sustainable food innovation that meets the demand for business models integrating circular blue-green economy principles. This study presents Lush Bites, a nutritional food product developed by valorizing shrimp head and onggok, two underutilized nutrient-rich by-products commonly discarded in Indonesia. The formulation process involved detoxification and drying techniques to ensure safety and nutritional retention. Nutritional values were estimated using reliable secondary data from Scopus-indexed publications, highlighting significant contributions of starch (72,43%) and astaxanthin (up to 160.06 μg/g). Organoleptic evaluation was conducted on 35 informed panelists with backgrounds in food science, showing a favourable acceptance, especially in taste and overall attributes (mean 4.0 on a 5-point scale). Lush Bites aligns with green and blue economy goals by turning food waste into a value-added product with a low cost production, supporting SDGs 2, 12, and 13. This research bridges theoretical findings from food waste valorization with practical application, demonstrating a profitable pathway for eco-friendly food production.